Clima laboral y su incidencia en la productividad en el centro de salud Venus Del Río, del Cantón Quevedo, año 2023 - Proaño Rizzo, Cinthya Xiomara (2024)
This research project highlights that the work environment influences the productivity, satisfaction and well-being of employees. The problem originates from the processes carried out in the organization and their impact on the work environment. The research seeks to identify problem areas and propose strategies to improve productivity and the work environment. This research is development in the Quevedo canton in the Venus del Río Health Subcenter, where since 2016 the reform to the General Regulations of the LOSEP establishes the technical standard to measure the work environment and organizational culture in the public sector at least once. once a year, by the Ministry of Labor. As is generally known, these types of evaluations carried out on a massive scale do not yield the expected results, therefore in this research the topic is discussed in depth directly with the staff of said institution, who are the main subjects of analysis within their environment. work, to obtain a precise result in relation to the variables proposed. Improving the work environment is crucial for effective and high-quality health care, especially in a public entity where the quality of free health care is affected by the work environment. To carry out this research, descriptive, exploratory and field research techniques were used, among the methods used were descriptive, inductive, deductive and combined qualitative and quantitative methods. Interviews were conducted with the director and three collaborators, as well as surveys with all staff at the Venus del Río Health Center to collect data on their perception of the work environment, their satisfaction and well-being. The data collected was analyzed using statistical techniques to identify patterns and correlations. This methodology allowed a comprehensive understanding of working conditions and their impact on staff productivity and satisfaction. The research results revealed that there are significant areas of dissatisfaction among employees, mainly related to lack of communication. Likewise, specific problems are identified in organizational processes that contribute to a negative work environment, in addition to a productivity index below that established as a goal.